Pola Konsumsi Beras Berdasarkan Golongan Pendapatan Rumah Tangga Masyarakat di Kecamatan Gerunggang Kota Pangkalpinang - Shinda, Shinda; Sitorus, Rostiar; Setiawan, Iwan (Universitas Galuh, 2024)
The aim of this research is to identify types of informal consumption in Gerunggang District, Pangkalpinang City based on informal income categories and is to identify factors that influence informal consumption in single household households in Gerunggang District, Pangkalpinang City. Types of informal consumption in Gerunggang District. Pangkalpinang City based on informal income categories and factors that influence informal consumption in household households in Gerunggang District, Pangkalpinang City. The technique used was purposive sampling, and the sample size was 108 people, each of which was divided into three categories based on the data. data collection period. A total of 36 samples have been classified as low, 36 samples as medium, and high. Least Squares (OLS) is used in multiple line regression analysis as a data cleaning method. to organize the data, SPSS 25 and Microsoft Excel 2010 were used. The results of the research show that in the low income group, the factor that influences meat consumption in rural areas in Gerunggang Regency is the number of family members; in the high income group, the factor is profit.